2010
DOI: 10.1111/j.1365-3156.2009.02453.x
|View full text |Cite
|
Sign up to set email alerts
|

Prices of antihypertensive medicines in sub-Saharan Africa and alignment to WHO’s model list of essential medicines

Abstract: Summaryobjective To investigate compliance of National Essential Medicines Lists (NEMLs) with the WHO Essential Medicines List (WHO ⁄ EML) in 2007 and to compare prices of antihypertensive drugs in and between 13 sub-Saharan African countries.methodology Data on NEMLs and drug prices were collected from 65 public and 65 private pharmacies (five of each per country). Prices were compared with the International Drug Price Indicator Guide (IDPIG). The cost of drug treatment within a country was calculated using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…A study in sub-Saharan Africa Percentage showed a strong presence of oral antihypertensive agents in EMLs, such as hydrochlorothiazide (85%), atenolol (77%), propranolol (92%), and nifedipine (85%), 19 similar to our analysis (90.1%, 87.9%, 90.1%, and 95.6%, respectively).…”
Section: Geographica and Income Distribution Of Identi Ed Emls In 14supporting
confidence: 79%
“…A study in sub-Saharan Africa Percentage showed a strong presence of oral antihypertensive agents in EMLs, such as hydrochlorothiazide (85%), atenolol (77%), propranolol (92%), and nifedipine (85%), 19 similar to our analysis (90.1%, 87.9%, 90.1%, and 95.6%, respectively).…”
Section: Geographica and Income Distribution Of Identi Ed Emls In 14supporting
confidence: 79%
“…SSA countries (63). In addition, at this low dose, dangerous side effects like hypokalemia (which can induce arrhythmias) are less expected.…”
Section: Beyond Protocols Suggested In the 2002 Who Cardiovascular Rimentioning
confidence: 99%
“…37 The list is a guide for national committees that are responsible for identifi cation of the most costeff ective medicines at country level for procurement, reimbursement, and treatment decisions, and helps to focus national eff orts towards universal coverage. A study 38 of 13 sub-Saharan African countries showed that only 38% of national lists were updated in the past 5 years. The investigators noted that antihypertensive drugs on national lists were substantially cheaper than were those not included, underscoring the role of the national list in ensuring fi nancial accessibility.…”
Section: Rational Selectionmentioning
confidence: 99%